2021
DOI: 10.3390/nu13041061
|View full text |Cite
|
Sign up to set email alerts
|

Polish Translation and Validation of the Mini Sarcopenia Risk Assessment (MSRA) Questionnaire to Assess Nutritional and Non-Nutritional Risk Factors of Sarcopenia in Older Adults

Abstract: A simple, short, cheap, and reasonably sensitive and specific screening tool assessing both nutritional and non-nutritional risk factors for sarcopenia is needed. Potentially, such a tool may be the Mini Sarcopenia Risk Assessment (MSRA) Questionnaire, which is available in a seven-item (MSRA-7) and five-item (MSRA-5) version. The study’s aim was Polish translation and validation of both MSRA versions in 160 volunteers aged ≥60 years. MSRA was validated against the six sets of international diagnostic criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
0
8
0
1
Order By: Relevance
“…It involves simple questions on age, physical activity level, consumption of regular meal, dairy products and protein, number of hospitalizations and weight loss in the last year. In addition to Chinese language validation in 2018, Polish language validation was performed very recently [30]. Polish versions of both MSRA-7 and MSRA-5 showed high sensitivity (about 85-90%) with commonly used sarcopenia definitions.…”
Section: Mini Sarcopenia Risk Assessment Questionnairementioning
confidence: 99%
“…It involves simple questions on age, physical activity level, consumption of regular meal, dairy products and protein, number of hospitalizations and weight loss in the last year. In addition to Chinese language validation in 2018, Polish language validation was performed very recently [30]. Polish versions of both MSRA-7 and MSRA-5 showed high sensitivity (about 85-90%) with commonly used sarcopenia definitions.…”
Section: Mini Sarcopenia Risk Assessment Questionnairementioning
confidence: 99%
“…The MSRA questionnaire in the Chinese language has been validated and it was concluded that the C-MSRA-5, compared with the C-MSRA-7, is a better tool for screening sarcopenia in community dwelling older adults [ 19 ]. The Polish versions of the MSRA presented good sensitivity, with better reliability of the MSRA-5 than the MSRA-7 when used as a screening tool for sarcopenia in community dwelling adults [ 20 ]. The Thai version of the MSRA-7 questionnaire provided more sensitivity with limited specificity than the MSRA-5 for screening sarcopenia in older patients at a medical outpatient clinic [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the MSRA as a pre-screening tool for sarcopenia was elaborated to be used in Italian subjects, it has been validated in the Brazilian Portuguese, Polish, Chinese, and Thai languages as well [ 18 , 19 , 20 , 21 ]. Thus, the MSRA questionnaire shows a high sensitivity as a screening tool compared with the SARC-F for sarcopenia risk assessment, its use being essential to detect early sarcopenia, which can lead to a diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is expected that hospitalized patients may be affected earlier by sarcopenia than outpatients; thus further studies are warranted to investigate older cancer patients; (4) The small sample size requires further validation and suggests caution in interpreting the data, and further studies are being conducted to investigate the inference of these findings using gold standard techniques; and (5) Inclusion of a single center diminishes the potential generalizability of data; thus, further studies are warranted to include more research centers. On the other hand, some positive points must be highlighted due to advantages for clinical practice: (1) it is an adaptation of a Brazilian Portuguese-translated version questionnaire for screening of sarcopenia risk in cancer patients, rather than Italian, Thai [ 8 ], and Polish [ 9 ]; (2) we suggest that associated with other nutritional assessment tools, the questionnaire will be useful for clinical practice in hospitals; and (3) the questionnaire is an easy-to use tool which will allow a fast screening for sarcopenia, especially in local hospitals with under-diagnosis of sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…MSRA is a questionnaire used for screening the sarcopenia that was elaborated to use in Italian subjects and has been validated in Chinese, Polish and Thai languages [ 5 , 6 , 8 , 9 ].…”
Section: Methodsmentioning
confidence: 99%